Chronic post-surgical pain after noncardiac surgery - Khan, James S (My University, 2015)
Chronic post-surgical pain (CPSP) is a debilitating complication of surgery. Despite increasing attention in recent years, there is a paucity of data on the incidence of CPSP after noncardiac surgery and the risk factors that affect its development. The studies in this thesis inform current knowledge gaps in the literature. Chapter 2 describes the interim results of a large, international prospective cohort study on the incidence of chronic incisional pain, a type of CPSP specific to the incision site, and its associated risk factors. Chapter 3 describes the association between postoperative patient coping and expectations about recovery after traumatic tibial fracture repair and the development of CPSP and its interference on normal work. Chapter 4 outlines methodological issues with pain measurement in clinical trials and describes a protocol for a randomized controlled trial that compares electronic data collection to traditional data collection methods when investigating CPSP.